Human exposure to mercury and its hematological effects: a systematic review - Angélica dos Santos Vianna; Elisabete Pedra de Matos; Iracina Maura de Jesus; Carmen Ildes Rodrigues Fróes Asmus; Volney de Magalhães Câmara (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Mercury is a metal found in the environment from natural and anthropogenic sources. It is highly toxic to ecosystems and living beings. Most human exposures come from ingestion of contaminated seafood, outgassing from dental amalgam or occupational exposure (e.g. gold mining), among other cases. Large populations are exposed to mercury, making it a very important issue from the public health perspective. Adverse health effects are commonly seen in the nervous system, but every organ is a potential target, such as the bone marrow. The main goal of this study was to assess the available evidence on human exposure to mercury and its hematological effects. A search strategy was constructed, including key terms (MeSH, text word and equivalents) for querying 2 repositories of master dissertation and PhD thesis (Fiocruz/ARCA and University of São Paulo) and 4 different electronic databases: BVS/LILACS, MEDLINE/PubMed, Scopus and TOXLINE/NIH, for articles published from 1950 to February 2018. There was no language restriction and a tool (EPHPP) was used to assess the quality of included studies. According to pre-established criteria, 80 studies were retrieved, all of them observational (48 case reports, 24 cross-sectional, 6 case series and 2 cohorts), comprising 9,284 people. Despite the fact that most exposed ones (6,012) had normal blood cell count and mercury hematological effects did not seem very usual (1,914 cases: 14 severe and 29 deaths), three studies reported association (β) for anemia, lymphopenia, neutrophilia and basophilia. We concluded that the gathered information pointed to mercury hematotoxic effects, some of them may be serious and even fatal.